(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
The author of this article conducted a study on the issue of enhancing the Republic of Uzbekistan’s position in the international gender index ratings and analyzed the work that is currently being conducted in this area. The institute employed the "Gender Inequality Index," "Gender Development" Index, "Gender Social Norms" Index of the United Nations Development Program, "Social Institutions and Gender" Index of the Development Center of the Organization for Economic Co-operation and Development, and "Global Women, Peace and Security" within the research framework. The evaluation methodologies of the indices were examined, and the educational indicators of Uzbekistan were analyzed.